2022
DOI: 10.3389/fphar.2022.982981
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of voriconazole and initial dosage optimization in patients with talaromycosis

Abstract: The high variability and unpredictability of the plasma concentration of voriconazole (VRC) pose a major challenge for clinical administration. The aim of this study was to develop a population pharmacokinetics (PPK) model of VRC and identify the factors influencing VRC PPK in patients with talaromycosis. Medical records and VRC medication history of patients with talaromycosis who were treated with VRC as initial therapy were collected. A total of 233 blood samples from 69 patients were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…Our study found that an increase in qCRP was related to a decrease in voriconazole CL, which has been widely confirmed in previous studies [ 39 , 51 , 52 , 53 , 54 , 55 , 56 ]. This is attributed to the fact that, in an inflammatory state, inflammatory mediators can bind to cytokine and toll-like receptor 4 receptors on the cell membrane and regulate the expression of transporters and drug-related metabolic enzymes through the NF-κB signaling pathway [ 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that an increase in qCRP was related to a decrease in voriconazole CL, which has been widely confirmed in previous studies [ 39 , 51 , 52 , 53 , 54 , 55 , 56 ]. This is attributed to the fact that, in an inflammatory state, inflammatory mediators can bind to cytokine and toll-like receptor 4 receptors on the cell membrane and regulate the expression of transporters and drug-related metabolic enzymes through the NF-κB signaling pathway [ 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is attributed to the fact that, in an inflammatory state, inflammatory mediators can bind to cytokine and toll-like receptor 4 receptors on the cell membrane and regulate the expression of transporters and drug-related metabolic enzymes through the NF-κB signaling pathway [ 57 ]. These findings suggested that metabolizing enzymes, including cytochrome P450 (CYP) isoenzymes, are downregulated by inflammatory cytokines, resulting in a decrease in voriconazole CL [ 56 , 58 ]. Furthermore, the inflammatory status may modulate polymorphisms in PK-related genes, which may influence the metabolic pathway from voriconazole to voriconazole N-oxide [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a robust association between C-reactive protein (CRP) and the efficacy of VRZ ( p = 0.0003), which is consistent with previous reports ( Chen et al, 2022 ; Jiang et al, 2022 ), demonstrating a significant impact of CRP on the pharmacokinetic profile of VRZ. Regrettably, only 44 CRP values were retrievable from the HIS, which were insufficient to provide a conclusive explanation for the efficacy observed in our final analysis.…”
Section: Discussionsupporting
confidence: 91%